Pengaruh Model Inquiry Terhadap Penguasaan Konsep dan Nilai Entrepreneur Pada Materi Inovasi Teknologi Biologi di SMA - Amelia Putri; Zulfiani Zulfiani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the effect of the inquiry model on concept mastery and entrepreneurial values in the material of biological technology innovation. The research was conducted with 10th-grade high school students in the academic year 2024/2025. A quantitative quasi-experimental method with a pretest-posttest design was used to assess the effect of the model on concept mastery, while a posttest-only design was used to evaluate entrepreneurial values. To obtain data on students' concept mastery after the treatment, a multiple-choice test was administered, while entrepreneurial values were assessed using a non-test method in the form of a questionnaire. The results of hypothesis testing through an Independent Sample T-Test yielded t-values of 15.367 and 16.692 with a significance level of less than 0.05 (sig = 0.0005 < 0.05). The conclusion of the study indicates that the inquiry learning model has an effect on students' concept mastery and entrepreneurial values in biological technology innovation at the high school level. Keywords: Biology, Entrepreneur, Inquiry Model, Concept Mastery